2018
DOI: 10.3354/meps12408
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variation and spatial distribution of decapod larvae in a region of persistent coastal upwelling

Abstract: The California Current System is characterized by strong coastal upwelling that drives high primary production with implications for life in the plankton. We investigated the role of environmental variability at local, regional, and basin-wide scales in determining decapod larval distributions across space and time over 8 yr (2004 to 2011). We focused on an area of the California Current off the coast of central California, USA, characterized by a strong upwelling jet, a retentive zone with high primary produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…In this work and previous studies, we have repeatedly sampled larval assemblages during many cruises over multiple locations and years (Morgan et al, 2009b,c;Morgan and Fisher, 2010;Hameed et al, 2018). In this work, we focused on the time and place of maximum upwelling, showing that larvae were not transported farther offshore at this region of strong, persistent upwelling, contrary to widespread expectations.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…In this work and previous studies, we have repeatedly sampled larval assemblages during many cruises over multiple locations and years (Morgan et al, 2009b,c;Morgan and Fisher, 2010;Hameed et al, 2018). In this work, we focused on the time and place of maximum upwelling, showing that larvae were not transported farther offshore at this region of strong, persistent upwelling, contrary to widespread expectations.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, the ability of larvae to regulate transport could have a large impact on dispersal and population connectivity and has been debated for decades. We recently determined that larvae occurred close to shore in persistent, strong upwelling on the Pacific Coast of the USA-rather than lost offshore as was widely expected (Morgan et al, 2009b(Morgan et al, ,c, 2011Morgan and Fisher, 2010;Fisher et al, 2014;Hameed et al, 2018)-and that larval mortality in the nearshore retention zone was much lower than previous estimates of larval mortality anywhere (White et al, 2014). We then demonstrated that larval behaviors enabling larvae to remain close to shore throughout development also enable them to settle near natal populations (Drake et al, 2013;Hameed et al, 2016).…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Nevertheless, benthic larvae in these regions are consistently retained near the coast, typically within a few kilometers of shore. These larval distributions are observed along the US west coast Hameed et al, 2018;Morgan and Fisher, 2010;Morgan et al, 2009aMorgan et al, , 2009bMorgan et al, , 2012Morgan, in press;Nickols et al, 2013;Shanks and Shearman, 2009), as well as upwelling regimes off Chile (Bonicelli et al, 2016;Poulin et al, 2002) and the Iberian Peninsula (Bartilotti et al, 2014;dos Santos et al, 2008;Domingues et al, 2012;MartaAlmeida et al, 2006). Larvae may avoid offshore transport by residing subsurface, where currents are weaker or onshore.…”
Section: Introductionmentioning
confidence: 99%